AB0232 Disease activity state in patients with rheumatoid arthritis included in the biobadabrasil registry. (12th June 2018) - Laurindo, I.M.M.; Pinheiro, M.; Macieira, J.; Duarte, A.; Kahlow, B.; Ranza, R.; Miranda, J.; Bertolo, M.; Valim, V.; Castro, G.; Lobato, M.D.F.; Titton, D.; et al.
Abstract : Objectives: to analyse disease activity of RA patients at the start of treatment with a biologic agent (adalimumab, infliximab, certolizumab, etanercept, golimumab, abatacept, rituximab and tocilizumab -bDMARDs), target (tofacitinib-tsDMARDs) therapy or conventional DMARDs (comparison cohort of RA patients – csDMARDs). Methods: BiobadaBrasil is a prospective observational cohort study, part of an international initiative (biobadaAmerica) in collaboration with BiobadaSeR; established in 2009, is an ongoing study supported by the Brazilian Society of Rheumatology (29 public centres located at academic instituitions and 2 in private practice) focused on the study of adverse events in patients on biologic therapy. Additionally, by decision of its investigators, disease activity scores were also recorded at the beginning of each treatment. Sex, age, disease duration, RA -DAS-28, concomitant treatments at baseline were collected. Results expressed in mean ±SD, %(n) Results: -Data from 1984 RA patients (67% on ts/bDMARDs) were analysed: 86% of the patients were women; mean age=56.6±14.95 years; disease duration=14.4±9.42; 87% RF positive. There were 3802 treatment courses, 67% with aTNF (Adalimumab-ADA, Certolizumab-CTZ, Etanercept-ETA, Golimumab-GOL, Infliximab-INFL), 33% non-aTNF (Abatacept-ABA, Rituximab-RIT, Tocilizumab-TCL) including Tofacitinib-TOF. The table 1 below depicted the medications prescribed at the initiation of a new treatment course: Considering the more recent medications patients beginning TCL have more active disease than the ones beginning GOL and CTZ (p<0, 006); anti-TNF are prescribed in association with MTX in less than 60% of the treatments. Extensive use of corticosteroids was identified besides consistent use of leflunomide and of hydroxychloroquine. Starting of new treatments was related to moderate/high levels of disease activity. Conclusions: patterns of bDMARDS, csDMARDS and corticosteroid use clearly surfaced. Possibilities of improvement can be addressed. Acknowledgements: for data monitoring P Cabral; contributing to BiobadaBrasil registry, R. Giorgi, H. Pereira, M. Scheinberg, F. Sztajnbok, W. Vieira Disclosure of Interest: None declared